The Influence of Entrepreneurship Education and Family Environment on Students’ Interest in Entrepreneurship - Aryati Arfah; Mapparenta Mapparenta; Serlin Serang (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to determine the influence of entrepreneurship education and family environment on the entrepreneurial motivation of students; the influence of entrepreneurship education, family environment, and entrepreneurial motivation on the students’ interest; and the influence of entrepreneurship education and family environment on entrepreneurial interest in entrepreneurial motivation mediation. This quantitative research type uses descriptive analysis methods and inferential statistics, namely Structural Equation Modeling (SEM). The population in this study was class XI students at a state Madrasah Aliyah in Makassar City. The researcher used stratified random sampling using the Slovin formulation to determine 100 social studies students as the sample. The data analysis carried out was path analysis which was processed using the SmartPLS program. The results of this study found that: 1) entrepreneurship education directly affects motivation; 2) family environment directly influences entrepreneurial motivation; 3) entrepreneurship education directly affects the interest in entrepreneurship; 3) entrepreneurship education directly affects the interest in entrepreneurship; 4) entrepreneurial motivation directly affects the interest in entrepreneurship; 5) entrepreneurship education affects an interest in entrepreneurship through the mediation of entrepreneurial motivation; 6) the family environment influences the interest in entrepreneurship through the mediation of entrepreneurial motivation.